Seasonal variation of cladocera in a perennial pond, Ambajogai (Maharashtra), India - Sakhare, Vishwas Balasaheb; Chalak, Ashwini Dnyandeo (Journal of Fisheries, 2020)
A systematic investigation on seasonal variations of cladocera in Udayan Sarovar, a perennial pond near Swami Ramanand Teerth Mahavidyalaya at Ambajogai (Maharashtra, India) was carried out for a period of one year from June 2018 to May 2019. A total of 9 species of cladocera were identified. The cladoceran diversity fluctuated seasonally and the maximum number of 240 organisms L–1 was recorded during month of April and minimum number of 22 organisms L–1 during the month of September.